Pengaruh pembebasan pajak UMKM terhadap kinerja usaha pada UMKM Kelurahan Tlogomas Kota Malang di masa Pandemi Covid-19 - Risnaningsih Risnaningsih; Hendrik Suhendri; Nuni Rosmiati Selan (University of Merdeka Malang, 2022)
This study was conducted to examine the effect of the MSME tax exemption on business performance during the COVID-19 pandemic in MSMEs in the Tlogomas village. The sampling technique using the Slovin formula was obtained a minimum sample of 32 respondents. Data analysis technique using simple linear regression test. The results showed that the MSME tax exemption had a positive and significant impact on business performance during the covid-19 pandemic.